Visions of annihilation : the Ustasha regime and the cultural politics of fascism, 1941-1945 - Yeomans, Rory (Series in Russian and East European studies., 2013)
The fascist Ustasha regime and its militias carried out a ruthless campaign of ethnic cleansing that killed an estimated half million Serbs, Jews, and Roma, and ended only with the defeat of the Axis powers in World War II. In this book, the author analyzes the Ustasha movement’s use of culture to appeal to radical nationalist sentiments and legitimize its genocidal policies. The author shows how the movement attempted to mobilize poets, novelists, filmmakers, visual artists, and intellectuals as purveyors of propaganda and visionaries of a utopian society. Meanwhile, newspapers, radio, and speeches called for the expulsion, persecution, or elimination of “alien” and “enemy” populations to purify the nation. This book describes how the dual concepts of annihilation and national regeneration were disseminated to the wider population and how they were interpreted at the grassroots level.